2019
DOI: 10.1002/path.5313
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of lymphoepithelioma‐like hepatocellular carcinoma

Abstract: Lymphoepithelioma‐like hepatocellular carcinoma (LEL‐HCC) is a distinct variant of HCC that is characterized by dense tumor‐infiltrating lymphocytes (TILs). Patients with LEL‐HCC also show better clinical outcomes compared to conventional HCC (c‐HCC), which is commonly presented with low TIL. Emerging evidence has begun to highlight tumor‐intrinsic genetic abnormalities in the tumor–host immune interfaces. However, genome‐wide characterization of LEL‐HCC remains largely unexplored. Here, we defined the genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Checkpoint inhibitors are monoclonal antibodies that block inhibitory checkpoint antigens and repress the stimulation of T cells, exhibiting anticancer effects (75,76). Upon chronic stimulation by tumor antigens, tumor-infiltrating T cells lose their effector functions and their ability to kill tumor cells, accompanied by a progressive increase in the diversity and number of inhibitory receptors expressed on them, including CD274, PDCD1LG2, HAVCR2, CTLA4, LAG3, PDCD1 and TIGIT (75)(76)(77)(78)(79)(80)(81)(82). Therefore, genes that were associated with immune checkpoints were selected for analysis in the present study.…”
Section: Il17amentioning
confidence: 99%
“…Checkpoint inhibitors are monoclonal antibodies that block inhibitory checkpoint antigens and repress the stimulation of T cells, exhibiting anticancer effects (75,76). Upon chronic stimulation by tumor antigens, tumor-infiltrating T cells lose their effector functions and their ability to kill tumor cells, accompanied by a progressive increase in the diversity and number of inhibitory receptors expressed on them, including CD274, PDCD1LG2, HAVCR2, CTLA4, LAG3, PDCD1 and TIGIT (75)(76)(77)(78)(79)(80)(81)(82). Therefore, genes that were associated with immune checkpoints were selected for analysis in the present study.…”
Section: Il17amentioning
confidence: 99%
“…Lymphocyte-rich HCCs are characterized by an immune rich stroma and have been demonstrated to have cirrhosis in only 46% of cases in a recent comprehensive review [104] . Molecular studies have revealed that mutations of CTNNB1, AXIN1, APC, NOTCH1 and NOTCH2 were less frequently observed in lymphocyte-rich HCCs than conventional HCCs [105] , suggesting a relation between these pathways and immune exclusion. In lymphoepithelioma-like HCC, oncogenes expressed from chromosome 11q13.3 (CCND1FGF19, and FGF4) are strongly associated with the immune checkpoint signature (CD274, PDCD1, BTLA, CTLA4, HAVCR2, IDO1, and LAG3).…”
Section: Dysregulation Of Molecular Pathways In Histological Variantsmentioning
confidence: 99%
“…In lymphoepithelioma-like HCC, oncogenes expressed from chromosome 11q13.3 (CCND1FGF19, and FGF4) are strongly associated with the immune checkpoint signature (CD274, PDCD1, BTLA, CTLA4, HAVCR2, IDO1, and LAG3). Such differences in genetic aberrations from classical HCCs provide insight into the need for therapeutic strategies that evade immune surveillance seen in classical HCCs [105,106] . Scirrhous HCC is another variant, which is less often associated with liver cirrhosis when compared with conventional HCC [55] .…”
Section: Dysregulation Of Molecular Pathways In Histological Variantsmentioning
confidence: 99%
“…While a few studies demonstrated a trend of better survival with this subtype [19][20][21]28] , the prognostic significance of this subtype remains to be clarified due to its rarity. The genomic landscape of 12 lymphocyte-rich HCC was determined by whole-exome sequencing in a recent report [32] . Mutations of CTNNB1, AXIN1, APC, NOTCH1 and NOTCH2 were less frequently observed in lymphocyte-rich HCC than conventional HCC.…”
Section: Lymphocyte-rich Hccmentioning
confidence: 99%